Corrosion failure of stainless-steel in caustic soda lines - Gaur, Bhupendra (Korose a ochrana materiálu, 2024)
The paper deals with the case studies of stainless steel piping corrosion in caustic soda transfer lines at a hydrocarbon processing plant, in the Asian region. The lines were in service of transferring the caustic soda solution from the storage tank farm to different process units, for subsequent use in reaction vessels. To maintain a minimum temperature of the fluid to avoid its precipitation, the lines were accompanied by a steam heat-tracer, throughout the line route. The material of construction (MOC) of the line was stainless steel type 316. After a period of about 3.5 years, 2” caustic line suffered fluid leakage, which was noticed through significant salt accumulation over insulation at one location. A valve was also noticed to leak through a weld at a 1.5” distribution line. The affected components were removed from service and subjected to detailed inspection and laboratory investigation, using advanced tools of metallurgical analysis and characterization. It was found that leakage in 2” line had occurred due to poor workmanship used during the repair of a manufacturing defect at the affected location and leakage of the valve had taken place due to the use of improper welding practice (in the case of subjected weld). In addition, the significant role of metallurgical defects in the parent metal was also disclosed to result in the observed failures. In addition, the contribution of process excursions can’t be completely ruled out. Finally, remedial measures are given to avoid the recurrence of such failure.